Dose response of exercise training following roux‐en‐Y gastric bypass surgery: A randomized trial. (5th November 2015) - Woodlief, Tracey L.; Carnero, Elvis A.; Standley, Robert A.; Distefano, Giovanna; Anthony, Steve J.; Dubis, Gabe S.; Jakicic, John M.; Houmard, Joseph A.; Coen, Paul M.; Goodpaster, Bret H.
Abstract : Objective: Roux‐en‐Y gastric bypass (RYGB) surgery can cause profound weight loss and improve overall cardiometabolic risk factors. Exercise (EX) training following RYGB can provide additional improvements in insulin sensitivity ( S I ) and cardiorespiratory fitness. However, it remains unknown whether a specific amount of EX post‐RYGB is required to achieve additional benefits. Methods: We performed a post hoc analysis of participants who were randomized into either a 6‐month structured EX program or a health education control (CON). The EX group ( n  = 56) was divided into tertiles according to the amount of weekly exercise performed, compared with CON ( n  = 42): low‐EX = 54 ± 8; middle‐EX = 129 ± 4; and high‐EX = 286 ± 40 min per week. Results: The high‐EX lost a significantly greater amount of body weight, total fat mass, and abdominal deep subcutaneous abdominal fat compared with CON ( P  < 0.005). S I improved to a greater extent in both the middle‐EX and high‐EX compared with CON ( P  < 0.04). Physical fitness (VO2 max) significantly improved in the high‐EX (9.3% ± 4.2%) compared with CON (−6.0 ± 2.4%) ( P  < 0.001). Skeletal muscle mitochondrial State 4 ( P  < 0.002) and 3 ( P  < 0.04) respiration was significantly higher in the high‐EX compared with CON. Conclusions: A modest volume of structured exercise provides additional improvements in insulin sensitivity following RYGB, but higher volumes of exercise are required to induce additional weight loss, changes in body composition, and improvements in cardiorespiratory fitness and skeletal muscle mitochondrial capacity.